2005
DOI: 10.1055/s-2005-870230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Opiates on Growth Hormone Secretion in Acromegaly

Abstract: Morphine at doses of 5 mg and 10 mg does not stimulate growth hormone (GH) secretion in normal subjects, and its effect on GH secretion in acromegaly is not widely documented. We investigated the effect of 15 mg intravenous morphine on growth hormone in patients with active acromegaly compared to normal subjects (7 acromegalics and 5 controls). Their mean (+/- SEM) age was 30.5 +/- 7.6 years and 29.5 +/- 0.5 years, respectively. Basal and peak response of growth hormone after morphine was measured with simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Continuous morphine exposure of male rats resulted in increased basal and mean GH concentrations, as well as in a modest increase of the GH pulse frequency but not of pulse amplitude; in females, morphine, apart from a marked reduction in the pulse amplitude, had little effect on other parameters of GH secretion (91). In human subjects, there are acute stimulatory effects of opioids on GH secretion which relate with the dose offered (92,93). Thus, intravenous morphine at doses of 5 mg and 10 mg did not promote GH secretion but a higher dose of 15 mg did (92,94,95).…”
Section: :4 R189 Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Continuous morphine exposure of male rats resulted in increased basal and mean GH concentrations, as well as in a modest increase of the GH pulse frequency but not of pulse amplitude; in females, morphine, apart from a marked reduction in the pulse amplitude, had little effect on other parameters of GH secretion (91). In human subjects, there are acute stimulatory effects of opioids on GH secretion which relate with the dose offered (92,93). Thus, intravenous morphine at doses of 5 mg and 10 mg did not promote GH secretion but a higher dose of 15 mg did (92,94,95).…”
Section: :4 R189 Reviewmentioning
confidence: 98%
“…In human subjects, there are acute stimulatory effects of opioids on GH secretion which relate with the dose offered (92,93). Thus, intravenous morphine at doses of 5 mg and 10 mg did not promote GH secretion but a higher dose of 15 mg did (92,94,95). Notably, administration of a Met-enkephalin analogue G-DAMME, in healthy men combined with a maximally stimulatory dose of a GHRH analogue resulted to an enhancing effect of the GHRHinduced GH release, suggesting that other mechanisms are also implicated (93).…”
Section: :4 R189 Reviewmentioning
confidence: 99%
“…[ 30 31 ] The increased serum leptin level decreases insulin sensitivity in some tissues, and the function of pancreatic beta-cells becomes deficient[ 32 ] and hyperinsulinism occurs. [ 31 33 ] On the contrary, Ferenczi et al . reported that the insulin plasma level was lower in morphine user with respect to normal group.…”
Section: Discussionmentioning
confidence: 99%
“…86 Acute administration of opioids in healthy humans has a dose-related stimulatory effect on GH production; intravenous administration of 15 mg morphine stimulated GH secretion, whilst smaller doses (5 and 10 mg) had no effect. [87][88][89] Studies on the impact of chronic opioid administration have shown conflicting results. Serum insulin-like growth factor 1 (IGF-1) levels were significantly lower in humans on intrathecal opioids (morphine and hydromorphone) for non-malignant pain compared to controls, with 15% (9/62) of the cases demonstrating suboptimal response to ITT (peak GH values <3 μg/L) and 17% (12/72) having IGF-1 concentrations more than two standard deviations below the mean.…”
Section: Somatotroph Axismentioning
confidence: 99%